A Nanoliposomal Gel Containing Cinnamomum zeylanicum Essential Oil with Effective Repellent against the Main Malaria Vector Anopheles stephensi. (22nd June 2022) - Osanloo, Mahmoud; Firoozian, Samira; Zarenezhad, Elham; Montaseri, Zahra; Satvati, Saha
Abstract : Malaria is the most important vector-borne disease; however, mosquito repellents are still a practical approach for controlling malaria, especially in endemic regions. Due to the side effects of synthetic repellents such as N, N -diethyl-meta-toluamide (DEET), the development of natural repellents has received much attention. In this study, nanoliposomes containing 0.5 and 2.5% w/v Cinnamomum zeylanicum essential oil were firstly prepared with particle sizes of 119 ± 6 and 195 ± 9 nm. Their morphologies and loading of the essential oil in the particles were then investigated using transmission electron microscopy (TEM) and attenuated total reflection-Fourier transform infrared (ATR-FTIR) analyses. The nanoliposomes were finally jellified to increase their viscosity and facilitate topical usage. The complete protection time of the nanoliposomal gel containing 2.5% C. zeylanicum essential oil was significantly longer than that of 2.5% DEET against Anopheles stephensi : 303 ± 10 > 242 ± 12 min, p < 0.001 . Moreover, the prepared nanoformulation was stable for at least six months at 4 and 26°C. Therefore, the prepared prototype could be considered a natural repellent against the main malaria mosquito vector in field conditions. In addition, it is suggested to be investigated against other important factors mosquitoes.